The Implementation of Akhlak Education Values in Academic Services at STIT Al Hikmah Tebing Tinggi - Lubis, Saiful Akhyar; Neliwati, Neliwati; Pardede, Ficki Padli (Universitas Malikussaleh, 2020)
This study article analyzes fonomena in implementing the values of moral education in academic services at STIT Al Hikmah Tebing Tinggi. The research method used in this research is qualitative with a phonomenology approach, which is to analyze the fonomenes in the implementation of the values of moral education at STIT Al Hikmah Tebing Tinggi. Based on the review of the explanation of the research results of the article above, it can be concluded that the following findings are that planning the implementation of moral education values in academic services by stipulating a standard rule of academic ethics involving lecturers, educational staff, and students. Implementing the implementation of moral education values in academic services by 1) providing an academic guidebook for the entire academic community that has been compiled by integrating the values of moral education. 2) Conducting public lectures to socialize about the academic ethics of STIT Al Hikmah Tebing Tinggi. 3) Oversee the development of the planning implementation by holding weekly meetings for the academic managers of STIT Al Hikmah Tebing Tinggi. 4) Provide sanctions and rewards for lecturers, students and exemplary education staff at STIT Al Hikmah Tebing Tinggi. Strategies in implementing the values of moral education in the learning process and academic services of STIT Al-Hikmah Tebing Tinggi by 1) Establishing academic ethics guidelines by integrating the values of moral education. 2) Building a sense of kinship through academic counseling, 3) modeling and habituation.